Nutrition status of nulliparous married women (15–24 years) in South Asia: trends, predictors, and program implications - Kumar, Abhishek; Sethi, Vani; Murira, Zivai; Prakash, Atma; Shrestha, Anita; Joe, William (Frontiers in Nutrition, 2024)
Introduction: Preconception nutrition, the nutritional status of women before pregnancy, is crucial for maternal and child health. Interventions focusing on preconception nutrition can help break the intergenerational cycle of malnutrition by improving the health and nutritional status of women before pregnancy. This study investigated the recent trends and patterns in the nutritional status of nulliparous adolescents and young women across six countries in South Asia: Bangladesh, India, Maldives, Nepal, Pakistan, and Sri Lanka.Methods: This study utilized the cross-sectional data from the Demographic and Health Survey (DHS) conducted between 2010 and 2022 for six South Asian countries. A total sample of 20024 nulliparous married women aged 15-24 years was analyzed to estimate the pooled prevalence for various anthropometric outcomes. Annual changes in the prevalence of the outcome indicators were presented for each country. Predictors of thinness and overweight were analyzed using logistic regression models.Results: Based on the latest rounds of DHS for respective countries, the pooled weighted prevalence of thinness was 24.4%, overweight was 24.8%, and short height was 11.3%. The prevalence of underweight ranged from 14.6% in Pakistan (DHS 2018) to 25.9% in India (DHS 2021). The least reduction in the prevalence of underweight was observed in India at 2.8% and Nepal at 0.7%. Based on the latest surveys, the mean BMI among women aged 15-24 years was the highest in Maldives (24.1, 95% CI: 23.4, 24.8) and Pakistan (22.9, 95% CI: 22.2, 23.5) and the lowest in India (20.9, 95% CI: 20.9, 21.0) and Nepal (20.8, 95% CI: 20.4, 21.2). The pooled prevalence of thinness and short height was high in rural areas (26.2 % and 11.8%), among less educated (28.1% & 14.5%), and bottom 40% wealth quintile groups (29.8% and 15.8%). Compared to young women (20-24 years), adolescent girls were 39% more likely to be underweight (OR: 1.39; 95% CI: 1.25,1.54).The findings highlight the need to broaden the scope of policies and programs designed for pregnant and lactating women so that nulliparous married women can be screened frequently for their anthropometric progress.